Kegagalan Inovasi Daerah di Kota Semarang (Studi Kasus : Inovasi Aplikasi i-Jus Melon Dinas Koperasi dan UMKM Kota Semarang) - Anggita Putri Hanintya; Dzuwanus Ghulam Manar (Journal of Politic and Government Studies, 2020)
Micro and Small Business licensing program based on technology and information on